Penyediaan Platform Digital dan Pendidikan Politik Pemilih Pemula Demi Suksesi Pemilu 2024 - Ahmady, Iqbal; Rassanjani, Saddam; Putri, Annisah (Ilin Institute, 2024)
This activity was carried out to fulfill the political education and community service responsibility before the political year. It was found that similar activities had never been carried out in the specified partners; this was because the institutions authorized to carry out political education activities among novice voters prioritized favorite schools so that vocational schools were rarely visited. This activity aims to raise awareness of the importance of political participation for novice voters to make their contribution meaningful to the country's sustainability. The method used to achieve this target is through providing political education material involving presenters who are experts in their fields. Apart from that, websites and social media are also used. Based on the results of the activities, the provision of digital media platforms is very influential in accommodating the aspirations and ideas of the younger generation. Providing socio-political content can also contribute to increasing feelings of patriotism and defending the country. So, the desire to participate in elections also increases.